Ultrasound impact on whey protein concentrate-pectin complexes and in the O/W emulsions with low oil soybean content stabilization - Albano, Kivia M. [UNESP]; Nicoletti, Vânia R. [UNESP] (Elsevier, 2018)
Consumers’ preference for products with reduced levels of fat increased in the last years. Proteins and polysaccharides have an important role due to their functional and interaction properties because, when combined in ratios and pH of higher potential for electrostatic interactions they may act as emulsifiers or stabilizers. This study evaluated the ultrasound impact on the electrostatic interaction between pectin (PEC) and whey protein concentrate (WPC) at different WPC:PEC ratios (1:1 to 5:1), and its effect on the emulsification and stability of emulsions formulated with WPC:PEC blends (1:1, 4:1) at low soybean oil contents (5 to 15%). Zeta potential analysis showed greater interactions between biopolymers at pH 3.5, which was proven in FTIR spectra. Rheology and turbidimetry showed that the ultrasound reduced the suspension viscosity and the size of the biopolymer complexes. Suspensions were Newtonian, whereas the emulsions showed shear-thinning behavior with slight increase in apparent viscosity as a function of oil content, and remained stable for seven days, with small droplets (<8 μm) stabilized and entrapped in a pectin network evidenced by confocal laser microscopy. Sonication was successfully applied to emulsion stabilization, improving the functional properties of WPC:PEC blends and enabling their application as low-fat systems, providing healthier products to consumers.
Keywords: Droplet size; Electrostatic interaction; Fat mimetics; Protein:polysaccharide ratio; Sonication; Viscosity